Oral health-related quality of life in children: Part II. Effects of clinical oral health status. A systematic review - TS Barbosa (Journal compilation 2008 Blackwell Munksgaard, 2008)
Children are affected by numerous oral and orofacial disorders, which have the potential to compromise functioning, well-being and the quality of life (QoL).